Triple jump phases: competitive progress specific pace and rhythm analysis - Oganjanov, A. L.; Nikitushkin, V. G.; Strizhak, A. P.; Mikhailov, N. G. (Theory and Practice of Physical Culture, 2021)
Objective of the study was to analyze the competitive progress specific triple jump control rhythm and aerial/ ground phase ratios for the men`s triple jump elite. Methods and structure of the study. We used for the purposes of the study photodiode video capturing Brower system with the triple jump replay analysis (using Dartfish software), with the tests and analyses assisted by marks in the triple jump sector. Subject to the analysis were the spatial and temporal rates of the aerial and ground phases in the triple jump sequence. 52 elite triple jump competitors qualified Class I to WCMS were sampled for the study to fix and analyze their individual best triple jump attempts to produce the temporal and spatial control rates. A total of 160 triple jump attempts were analyzed during the Russian and international competition.